PRESENCE OF LEAD (PB) FROM RODENTS AND FROM ITS PARASITE, HYMENOLEPIS SP. - Jessah Mae A. Flores1*, Diane Shiela C. Castillo2, Luzviminda S. Quitos2 (Chelonian Research Foundation, 2023)
The Muridae or the murid rodents have known to exist in agroecosystems as pests and are widely used for the determination of the level of environmental contamination based on the concentration of heavy metals in their different organs, tissues or in whole bodies. Helminthic parasites from its host, are also known to accumulate a high amount of lead concentration from their surroundings. This study addresses the Sustainable Development Goals (SDG 15) – Life on Land which is to protect, restore and promote sustainable use of the ecosystem and to halt the biodiversity loss by determining the presence of lead from rodents and its Hymenolepis species in an agroecosystem site. From a total of 41 individuals collected rodents namely, Rattus norvegicus and Rattus tanezumi, 73.17% of these were positive with Hymenolepis sp. A representative sample of infected rodents from each sampling station was analyzed for lead analysis. The concentration of lead in the kidney of collected rats as well as their parasite Hymenolepis sp. were determined and found to be negative for the presence of lead excluding the helminth parasite from Rattus norvegicus gathered from residential areas with 0.0086 ppm. The low level and not detectable results provide evidence that the areas in the study including commercial, agricultural and residentials have a low risk in heavy metal contamination which means that the possible lead exposure were absent to the habitat of the rodents. Possible factors influencing the low lead exposure in host tissue and its helminth parasite should be further determined as well as the factors affecting the abundance of R. tanezmi with regards to its behavior in agricultural habitat. Keywords: rodents; lead; parasite; Hymenolepis sp.